Orphanhood and the long-run impact on children - Beegle, K; De Weerdt, J; Dercon, S (2007)
This paper presents unique evidence that orphanhood matters in the long-run for health and education outcomes, in a region of Northwestern Tanzania. We study a sample of 718 non-orphaned children surveyed in 1991-94, who were traced and reinterviewed as adults in 2004. A large proportion, 19 percent, lost one or more parents before the age of 15 in this period, allowing us to assess permanent health and education impacts of orphanhood. In the analysis, we can control for a wide range of child and adult characteristics before orphanhood, as well as community fixed effects. We find that maternal orphanhood has a permanent adverse impact of 2cm of final height attainment and one year of educational attainment. Expressing welfare in terms of consumption expenditure, the result is a gap of 8.5 percent compared to similar children whose mother survived till at least their 15th birthday.